1997
DOI: 10.1016/s0300-5712(96)00048-6
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and radiographic evaluation of four adhesive systems

Abstract: Objectives: The purpose of this study was to compare micro leak age, gap formation, thickness of the adhesive layer and its radiographic appearance associated with four adhesive restorative procedures for class 1 cavities. Methods: Adhesive systems with easy handling characteristics were selected for the restoration of class I cavities in extracted third molars. Bite wing radiographs were taken of each tooth and four observers were asked to assess the presence of the adhesive layer. Microleakage, gap width and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…It has been reported that the adhesives of the one-bottle systems create thinner adhesive layer than those of the self-etching primer systems. 17,18 Clearly, a thin adhesive layer favors fluoride release from the coated material. Hence, the adhesives of the one-bottle systems which contain solvents may produce thinner layers of adhesive, promoting greater fluoride release from the restorative material.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the adhesives of the one-bottle systems create thinner adhesive layer than those of the self-etching primer systems. 17,18 Clearly, a thin adhesive layer favors fluoride release from the coated material. Hence, the adhesives of the one-bottle systems which contain solvents may produce thinner layers of adhesive, promoting greater fluoride release from the restorative material.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the filled adhesive, the increased viscosity and the role of the oxygen inhibition layer is a major cause of thick bonding layers 6) . Opdam et al 16) reported that thick adhesive layer seems to prevent the formation of interfacial gaps between tooth and restoration and act as a superior elastic buffer compared to thinner layers, whereas Hilton and Schwartz 17) suggested that thick adhesive layer adversely affects bond strengths, increases crack propagation, elevates the thermal co-efficient of expansion mismatch with the tooth and decreases the load bearing and wear component of the restoration.…”
Section: Part ⅰ Adhesive Thicknessmentioning
confidence: 99%
“…During mastication, saliva and other liquids may enter the gaps under pressure, resulting in detachment of the adhesive interface, or deformation of restoration margins. 2 This in turn may allow further penetration of saliva and microorganisms into the tooth-composite interface, bringing discoloration, hypersensitivity, plaque accumulation, and may potentially lead to the development of a caries lesion, which is the main reason for composite restorations to be replaced. 3 However, this costly procedure can be delayed as long as possible with early detection and monitoring of gap or defect progression adjacent to restorations.…”
Section: Introductionmentioning
confidence: 99%